Revitalisierung nach Trauma, Episode VI: Revitalisierung nach Trauma (Das Erwachen der Pulpa) - Galler, Kerstin Martina (Oralprophylaxe und Kinderzahnheilkunde, 2023)
Dental trauma may result in pulp necrosis, which entails an arrest of root development. Revitalization is an established method to enable formation of new tissue inside the root canal. The indication for this procedure is given in imature teeth with pulp necrosis, which is identical with the indication for the apical plug. The benefit of revitalization is the potential hard tissue apposition, which can strengthen fracture-prone root walls in immature teeth. Therefore, revitalization is recommended in particular for teeth with early stages of root development.
CRIS-Team Scopus Importer:2023-11-24
Keywords: Dental pulp regeneration; Dental trauma; Pulp necrosis; Revitalization; Root formation